2020
DOI: 10.1371/journal.pone.0232738
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and healthcare resource utilization in palmoplantar pustulosis patients in Japan: A claims database study

Abstract: BackgroundPalmoplantar pustulosis (PPP) is a chronic, relapsing, inflammatory autoimmune condition, characterized by sterile pustules on the palms and soles. The treatment patterns of PPP and total health care resource utilization in Japan are not well described. Investigating these areas is needed to understand current PPP management in Japan. ObjectiveTo describe the characteristics, medication treatment and health care resource utilization patterns, and associated costs of PPP patients in Japan. MethodsA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…Infliximab, certolizumab pegol, risankizumab, tildrakizumab, ixekizumab, and methotrexate were not evaluated owing to a small sample size (<20 patients each). Treatment discontinuation was defined as having no prescription of the index systemic treatment for at least 60 days following the period covered by the last prescription 22,24,27,28 . The time to treatment discontinuation was defined as the time from the index date to the date of treatment discontinuation, i.e., the last day of the period covered by the last prescription.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infliximab, certolizumab pegol, risankizumab, tildrakizumab, ixekizumab, and methotrexate were not evaluated owing to a small sample size (<20 patients each). Treatment discontinuation was defined as having no prescription of the index systemic treatment for at least 60 days following the period covered by the last prescription 22,24,27,28 . The time to treatment discontinuation was defined as the time from the index date to the date of treatment discontinuation, i.e., the last day of the period covered by the last prescription.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment discontinuation was defined as having no prescription of the index systemic treatment for at least 60 days following the period covered by the last prescription. 22 , 24 , 27 , 28 The time to treatment discontinuation was defined as the time from the index date to the date of treatment discontinuation, i.e., the last day of the period covered by the last prescription. The systemic treatments of interest and their treatment intervals are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is similar to a claims database publication from Japan which reported a large proportion of PPP patients continued topical steroids in addition to systemic therapies. 12 In this retrospective study, apremilast, followed by ustekinumab and guselkumab, appeared to provide the most promising results out of the systemic agents used due to the highest adherence rates. Although the few patients remaining on acitretin, alitretinoin and methotrexate had a good response achieving “clear” or “almost clear”, the proportion of patients remaining on these therapies was low and the majority of patients had discontinued therapy due to adverse events or lack of efficacy.…”
Section: Discussionmentioning
confidence: 82%
“…The estimated prevalence of GPP ranges from 1.76 per million in Europe to 7.46 per million in Japan [13,14]. The estimated prevalence of PPP ranges from 0.01% and 0.05% [15]; although, one large Japanese study reported a national prevalence of 0.12% [12].…”
Section: Further Informationmentioning
confidence: 99%